INCLUSIVE REHABILITATION PROGRAMS FOR CHILDREN WITH HEARING IMPAIRMENTS - Gavhar Saparovna Abdullayeva (Modern American Journals, 2025)
This article presents the features of auditory-speech perception and speech development of hard-of-hearing and deaf children using modern means of hearing prosthetics – cochlear implants. The conditions favorable for the education and upbringing of children with cochlear implants are considered. Recommendations for teachers on the organization of the necessary conditions for the education and upbringing of such children in school educational institutions are presented.
Keywords: Inclusive education, children with hearing impairment, cochlear implantation, methods, educational, school.